Analysis Of Students’ Knowledge Of Dengue Hemorrhagic Fever (Dhf) Prevention At The Faculty Of Medicine And Health Sciences, Universitas Jambi - Shandy Tri Winata; Dwi Noerjoedianto; Budi Aswin; M. Ridwan; Ashar Nuzulul Putra (CV. AFDIFAL MAJU BERKAH, 2026)
Dengue Hemorrhagic Fever (DHF) remains an important public health problem in Indonesia, particularly in tropical regions where Aedes mosquitoes can breed easily. Knowledge is one of the key factors that supports preventive behavior, especially among university students who are expected to become future health promoters. This study aimed to analyze the level of knowledge of Public Health students regarding DHF prevention at the Faculty of Medicine and Health Sciences, Universitas Jambi.This quantitative study used a descriptive cross-sectional design and was conducted from February to March 2026. The sample consisted of 98 students selected using purposive sampling. Data were collected using a closed-ended questionnaire consisting of 20 true-false items. All questionnaire items were valid (r count > 0.361), and the instrument showed good reliability (Cronbach’s Alpha = 0.823). Data were processed through editing, coding, scoring, entry, and cleaning, then analyzed descriptively using frequency distributions and percentages.The results showed that 92 students (93.9%) had good knowledge and 6 students (6.1%) had poor knowledge. The highest indicator scores were found in knowledge of DHF symptoms and the role of individuals and the environment in prevention (99.0%), while the lowest indicator score was found in preventive efforts (93.4%). At the item level, the lowest correct response was found in the statement that fogging is the only method of preventing DHF, with 69.4% correct responses.In conclusion, most students had good knowledge of DHF prevention. However, strengthening specific understanding of integrated prevention strategies, particularly the limited role of fogging, is still needed.